Decreased WNT3 expression in chronic lymphocytic leukaemia is a hallmark of disease progression and identifies patients with worse prognosis in the subgroup with mutated IGHV. (21st September 2016) - Poppova, Lucie; Janovska, Pavlina; Plevova, Karla; Radova, Lenka; Plesingerova, Hana; Borsky, Marek; Kotaskova, Jana; Kantorova, Barbara; Hlozkova, Michaela; Figulova, Jana; Brychtova, Yvona; Machalova, Michaela; et al.
Summary: The canonical Wnt pathway, dependent on β‐catenin‐controlled transcription, is the most explored Wnt pathway, known to drive the malignant transformation of multiple cell types. Several reports have suggested that this pathway also participates in chronic lymphocytic leukaemia (CLL) pathogenesis. To get a better insight into the role of the Wnt/β‐catenin pathway in CLL we analysed in detail the expression of the most overexpressed Wnt ligand, encoded by the WNT3 gene, in a well‐defined cohort of 137 CLL patients. Our analysis demonstrated that (i) untreated patients with more aggressive disease (with a notable exception of patients with 11q deletion) express less WNT3, (ii) WNT3 declines with disease progression in a significant proportion of patients and (iii) low WNT3 was identified as a strong independent marker indicating shorter treatment‐free survival in CLL patients with IGHV mutation. Interestingly, CLL‐related lymphoid cell lines, but not stromal cells, failed to respond to the ligand‐induced activation of the Wnt/β‐catenin pathway. This opens the possibility that CLL cells use Wnt‐3 to communicate with the cells in the microenvironment. We thus propose that the Wnt/β‐catenin pathway plays a more complex role in CLL pathogenesis than previously anticipated.